Fmoc-PEG Coated Single-Wall Carbon Nanotube Carriers by Non-covalent Functionalization: An Experimental and Molecular Dynamics Study - Yeniyurt, Yesim; Kilic, Sila; Güner-Yılmaz, Ö. Zeynep; Bozoglu, Serdar; Meran, Mehdi; Baysak, Elif; Kurkcuoglu, Ozge; Hizal, Gurkan; Karatepe, Nilgun; Batirel, Saime; Güner, F. Seniha (Frontiers in Bioengineering and Biotechnology, 2021)
Due to their structural characteristics at the nanoscale level, single-walled carbon nanotubes (SWNTs), hold great promise for applications in biomedicine such as drug delivery systems. Herein, a novel single-walled carbon nanotube (SWNT)-based drug delivery system was developed by conjugation of various Fmoc-amino acid bearing polyethylene glycol (PEG) chains (Mw = 2000, 5000, and 12000). In the first step, full-atom molecular dynamics simulations (MD) were performed to identify the most suitable Fmoc-amino acid for an effective surface coating of SWNT. Fmoc-glycine, Fmoc-tryptophan, and Fmoc-cysteine were selected to attach to the PEG polymer. Here, Fmoc-cysteine and -tryptophan had better average interaction energies with SWNT with a high number of aromatic groups, while Fmoc-glycine provided a non-aromatic control. In the experimental studies, noncovalent modification of SWNTs was achieved by Fmoc-amino acid-bearing PEG chains. The remarkably high amount of Fmoc-glycine-PEG, Fmoc-tryptophan-PEG, and Fmoc-cysteine-PEG complexes adsorbed onto the SWNT surface, as was assessed via thermogravimetric and UV-vis spectroscopy analyses. Furthermore, Fmoc-cysteine-PEG5000 and Fmoc-cysteine-PEG12000 complexes displayed longer suspension time in deionized water, up to 1 and 5 week, respectively, underlying the ability of these surfactants to effectively disperse SWNTs in an aqueous environment. In vitro cell viability assays on human dermal fibroblast cells also showed the low cytotoxicity of these two samples, even at high concentrations. In conclusion, synthesized nanocarriers have a great potential for drug delivery systems, with high loading capacity, and excellent complex stability in water critical for biocompatibility.